Trade-off between photovoltaic systems installation and agricultural practices on arable lands: An environmental and socio-economic impact analysis for Italy. (November 2016) - Sacchelli, S.; Garegnani, G.; Geri, F.; Grilli, G.; Paletto, A.; Zambelli, P.; Ciolli, M.; Vettorato, D.
Highlights: A GIS multiscale model for photovoltaic solar energy estimation is developed. The model introduces in the analysis socio-economic and environmental constraints. We model the trade-off among solar energy and crops production. The flexible and multistep approach defines a practical Decision Support System. Abstract: The paper introduces and discusses an open-source spatial-based model (called r.green.solar ) able to quantify the energy production from solar photovoltaic (PV) ground-mounted panels. Socio-economic and environmental impacts can be evaluated by the model. The model starts from the theoretical quantity of solar PV potential energy and estimates a reduction of total amount of energy based on legal, technical, recommended and economic constraints. Model outputs were used for a trade-off analysis between energy production and traditional crops for food/feed cultivation on not irrigated arable land. The model was tested at regional level for a Mediterranean context (Italy). The results confirm that the economic profitability of PV systems follows a north-south gradient, but the main impacts are related to local peculiarities – such as the disposal of not irrigated arable land and the presence of constraints, in particular the landscape maintenance, the morphological variables and the specialization index – and crop yields.